Nonoperative Management of Acute Upper Limb Ischemia. (June 2016) - Wong, Victor W.; Major, Melanie R.; Higgins, James P.
Background: Acute upper limb ischemia (AULI) is an uncommon emergency warranting immediate evaluation and treatment. The role of nonsurgical therapies including endovascular techniques, thrombolytics, and anticoagulation remains undefined. The authors systematically reviewed the current literature on the nonsurgical treatment of acute ischemia of the upper extremity.Methods: A PubMed and Embase search was conducted, and articles were screened using predetermined criteria. Data collected included patient demographics, cause of upper limb ischemia, type of nonsurgical treatment used, treatment outcomes, and complications. Patients were divided into 4 treatment groups: catheter embolectomy, catheter-directed thrombolysis, endovascular stenting, and anticoagulation/medical therapy alone.Results: Twenty-three retrospective studies met the search criteria. Of 1326 reported occlusions, 92% (1221) were attributed to thromboembolic disease. The second most common cause was iatrogenic (1.5%). Overall limb salvage rates were excellent with catheter embolectomy (862 of 882 cases, 97.7%) and catheter-directed thrombolysis (110 of 114 cases, 96.5%). Limb salvage rates were also high with anticoagulation/medical therapy (158 of 165 cases, 95.8%), but poor functional outcomes were more often reported.Conclusions: High-quality evidence to guide the nonsurgical treatment of AULI is lacking. Retrospective studies support the utility of catheter-based embolectomy and thrombolysis for distal ischemia. Whether a surgical or nonsurgical approach is taken, anticoagulation therapy remains a mainstay of both treatment and prevention of AULI. Because AULI patients often have underlying cardiac and/or systemic disease, a multidisciplinary approach is essential to minimize complications and prevent future occurrences.